PRAGMATICS ACQUISITION OF FIVE-YEARS OLD INDONESIAN CHILDREN IN CASUAL CONVERSATION - Evaline Roslina Simanjuntak; Busmin Gurning; Sumarsih Sumarsih (LINGUISTIK TERAPAN, 2018)
This research was aimed at finding out the pragmatics acquisition of five-years old Indonesian children in casual conversation. The objectives of this descriptive qualitative research were to: (1) find the type of the pragmatics acquired by a five-years-old child, (2) to find out the way of how do the five years old Indonesian children acquired  the pragmatics in casual conversation, and (3) to find out the reason of why do the five years old Indonesian children acquired  the pragmatics in this way. The data were obtained from three Indonesian boy children who lived in Batakness environment where most of their friends spoke in Batakness language. This study was located at lintongnihuta, Humbang Hasundutan regency. In collecting the data. this study applied documentation with audio visual recorder as the instrument of collecting the data. The technique of data analysis used in this study was descriptive technique, and the data were described trough the process of transcribing the data and reducing the data by the process of selecting, focusing, simplifying and transforming the transcripts of the data, after that, displaying the data and at last drawing the conclusions. The finding indicates that the subject of this study had mastered pragmatics, were the types of pragmatics acquired are exchange structures, turn taking, repairs, and cohesion. While the most dominant pragmatics used was turn taking. The way of  five years-old Indonesian children acquire the pragmatics in casual conversation were by united the environment’s effect, culture, habits, mood, and their focus on their own mind, needs, and what they were thinking about. And the dominant affected by focusing to their mind only. Then based on the interview with their parents and other caregivers, it’s found that the reason of using pragmatics in highest frequency were because the children often focused to the things in their mind only.Keywords: Pragmatics, Acquisition, Indonesian Children, Casual Conversation